Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 9, 1929 - Hawley, Joseph Roswell (The Hartford Times, Inc., 1929)
Letters of General Joseph R. Hawley to Charles Dudley Warner, The Hartford Daily Times, December 09, 1929. Events moved rapidly towards the break between the North and the South. In February, a peace conference had been called to meet in Philadelphia and on the same day, delegates gathered at Montgomery, Alabama to form a southern confederacy. Beyond the middle of that month, this organization was completed and Jefferson Davis was elected president. In March, Lincoln took oath as president and the South viewed his inaugural address as a virtual declaration of war. The only question was when the powder magazine would be exploded. On April 14th, Fort Sumter was fired on, and the country plunged into civil war.
1 electronic record. Scanned newspaper article. 2 image scans. 1.38 MB (1,454,186 bytes). 2 PDF copies (Master: PDF/A fmt/477; Access: reduced sized PDF fmt/19). 41.4 MB (43,477,681 bytes).
Keywords: United States--History--Civil War, 1861-1865; Hawley, Joseph R. (Joseph Roswell), 1826-1905; American Civil War (United States : 1861-1865); Personal correspondence; Letters; Newspapers